The relation between 1 Thessalonians and 2 Thessalonians and the inauthenticity of 2 Thessalonians - Verhoef, Eduard (Hervormde teologiese studies, 1997)
The relation between 1 Thessalonians and 2 Thessalonians is a disputed question. Many scholars argue that 2 Thessalonians is pseudepigraphic, written one or more decades after 1 Thessalonians. Others defend the authenticity of 2 Thessalonians. Wanamaker argues in his recent commentary that 2 Thessalonians was written before 1 Thessalonians. In this way the problems raised by the complicated relation between the two letters would be solved. Wanamaker argues that Timothy on his visit to Thessalonica (1 Thes 3:1-5) brought the letter we call 2 Thessalonians. Lecompte argues that Silas wrote 1 Thessalonians and that Paul himself is the author of 2 Thessalonians, so he could correct the misunderstandings caused by Silas's writing. Or perhaps Silas did not exactly write what Paul had agreed with his co-workers. I will argue in this article that the arguments used by Wanamaker and Lecompte are invalid for grammatical reasons. The great resemblance between 1 Thessalonians and 2 Thessalonians in spite of these different opinions, is best explained if we see 2 Thessalonians as a pseudepigraphic epistle.